Dense Water Formation in the North–Central Aegean Sea during Winter 2021–2022 - Manos Potiris; Ioannis G. Mamoutos; Elina Tragou; Vassilis Zervakis; Dimitris Kassis; Dionysios Ballas (Journal of Marine Science and Engineering, 2024)
The evolution and drivers of dense water formation (DWF) in the North–Central Aegean Sea (NCAeg) during winter 2021–2022 are studied using observations from two Argo floats and the output of an operational data-assimilating model. Dense water with σθ>29.1 kgm−3 was produced over most of the NCAeg, except for the northeastern part covered by Black Sea water (BSW), where the maximum surface density was